A Primary Study of Tracking Photovoltaic System for Mobile Station in Malaysia - Ahmad Fudholi; Lim Chin Haw; Kamaruzzaman Sopian; Ahmed Mohamed Omer Abdulmula (Institute of Advanced Engineering and Science, 2018)
This paper describes the performance of tracking photovoltaic (PV) system for mobile station. The system consists of tracking PV array, the battery bank, the maximum power point tracking (MPPT) controller and the DC/AC inverter). This system is the first full solar power station, which acts as pilot project by Celcom Sdn. Bhd. Success of this system shows potential of electrify rural remote area. The design is hoped to be a pioneer and acts as well-known system in order to ensure renewable energy is the future supply of electricity in far located urban area. This paper showes the record of the battery state-of-charge (SOC) as a function of time for rainy and sunny days.